Effect of nanoparticles in molten salts – MD simulations and experimental study. (June 2020) - Svobodova-Sedlackova, Adela; Barreneche, Camila; Alonso, Gerard; Fernandez, A. Inés; Gamallo, Pablo
Abstract: Highlighted experimental studies on nanofluids reveal an anomalous increment in the specific heat capacity ( C p ) of these ionic systems when nanoparticles are added. This fact is really important due the applicability of nanofluids in concentrating solar power plants as heat transfer fluid and storage media. These are promising results for the development of high-temperature heat storage applications by enhanced storage capacity materials. The present work focuses on the study of this effect in NaNO3 molten salt doped with SiO2 nanoparticles by molecular dynamics (MD) simulations and Differential Scanning Calorimetry (DSC) experiments. The study shows that for nanoparticles' concentrations around 1% wt. the C p increases by 26% compared to pure NaNO3, whereas at higher concentrations the effect disappears. The results approach high agreement between experimental and simulation results and MD simulations reveal that the increase of C p at low concentrations is explained by the formation of a semi ordered layer of ionic fluid. This layer is rich in Na + cations, around the nanoparticles whereas the reduction of C p at concentrations higher than 2% wt. is related to the aggregation of nanoparticles as revealed by Scanning Electron Microscopy (SEM). However, deep experimental results with other materials will be required in order to validate the layering effect. Graphical abstract: Three mechanisms have been proposed as candidates to explain the unconventional C p increment phenomenon in nanofluids. Adapted from Ref. (6). Mechanism I: The superficial atoms of the nanoparticles are less limited since they have a smaller number of bonds. Therefore, this superficial atom oscillates at lower natural frequencies and high amplitudes, resulting in a higher superficial energy. Mechanism II: The interaction of nanoparticle's surface atoms with the ionic salt. Mechanism III: The presence of a semi-solid layer around the nanoparticles surface contributes to the C p increment of the nanofluid. Image 1 Highlights: NaNO3 based nanofluid has a limit concentration around 2%wt. for the Cp improvement. MD results show similar trend than Cp measured with DSC of 5–15 nm nanoparticles. Analysis of the ρ(r) shows a layer formation on the nanoparticle surface. The semi-solid layering mechanism is observed to explain the non-conventional Cp .